An ApoA-I Mimic Peptide of 4F Promotes SDF-1α Expression in Endothelial Cells Through PI3K/Akt/ERK/HIF-1α Signaling Pathway - Lv, Kaixuan; Kong, Lingyu; Yang, Mei; Zhang, Linlin; Chu, Shangmin; Zhang, Lichun; Yu, Jielun; Zhong, Guoshen; Shi, Yanhua; Wang, Xia; Yang, Nana (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) seriously impairs the health of human beings and is manifested initially as endothelial cells (ECs) impairment and dysfunction in vascular intima, which can be alleviated through mobilization of endothelial progenitor cells (EPCs) induced by stromal cell-derived factor-1α (SDF-1α). A strong inverse correlation between HDL and AS has been proposed. The present work is to investigate whether 4F, an apolipoprotein A-I (apoA-I, major component protein of HDL) mimic peptide, can up-regulate SDF-1α in mice and human umbilical vein endothelial cells (HUVECs) and the underlying mechanism. The protein levels of SDF-1α were measured by ELISA assay. Protein levels of HIF-1α, phosphorylated Akt (p-Akt) and phosphorylated ERK (p-ERK) were evaluated by Western blotting analysis. The results show that L-4F significantly up-regulates protein levels of HIF-1α, Akt, and ERK, which can be inhibited by the PI3K inhibitor, LY294002 or ERK inhibitor, PD98059, respectively. Particularly, LY294002 can down-regulate the levels of p-ERK, while PD98059 can not suppress that of p-Akt. D-4F can up-regulate the levels of HIF, p-Akt, and p-ERK in the abdominal aorta and inferior vena cava from mice. These results suggest that 4F promotes SDF-1α expression in ECs through PI3K/Akt/ERK/HIF-1α signaling pathway.